The Importance and Usage of Clay Minerals in Industry - Rasouli, Hafizullah (Journal of Natural Sciences – Kabul University, 2021)
Clay minerals are important in various sections of industry and are also used in the reconstruction of geological processes. Generally, clay minerals are involved in the interpretation of geological processes in sedimentary basins. As a result, materials join and are reconstructed by fine materials. Different soil layers form distinct phases and rock cycles in nature. Most diagenetic processes are also associated with clays. Clay minerals are used in industries such as the production of kaolin, paint, paper, and ceramics. Additionally, in construction projects such as roads, dams, retaining walls, airports, and filling earth with soft materials, clay minerals are needed for compaction to eliminate all pores between solid particles. When specific clay minerals, such as smectite, mix with other construction materials, the infiltration of water causes expansion, increasing volume, and after dehydration, the volume reduces. As a result, the relative construction can become damaged or eroded.